Identification of Transcriptional Variation in Aortic Remodeling Using a Murine Transverse Aortic Constriction (TAC) Model - Zhang, Xinlu; Feng, Ting; Zeng, Xin-Xin I.; Liang, Hongbin; Situ, Bo; Zhang, Qiuxia; Zhou, Fengyun; Chen, Yejia; Wang, Tao; Cai, Du; Lin, Xinxin; Xiu, Jiancheng; et al. (Frontiers in Cardiovascular Medicine, 2020)
Arterial remodeling is a major pathological consequence of hypertension, which is recognized as the most common chronic non-communicable disease. However, the detailed mechanism of how arterial remodeling is induced by hypertension has not yet been fully elucidated. Evaluating the transcriptional changes in arterial tissue in response to elevated blood pressure at an early stage may provide new insights and identify novel therapeutic candidates in preventing arterial remodeling. Here, we used the ascending aorta of the transverse aortic constriction (TAC) model to induce arterial remodeling in C57BL/6 male mice. Age-matched mice were subjected to sham surgery as controls. The TAC model was only considered successful if the mice conformed to the criteria (RC/LC blood flow velocity with 5–10-fold change) 1 week after the surgery. Two weeks after surgery, the ascending aorta developed severe remodeling in TAC mice as compared to the sham group. High throughput sequencing was then applied to identify differentially expressed (DE) transcripts. In silicon analysis were then performed to systematically network transcriptional changes. A total of 1,019 mRNAs were significantly changed between TAC and the sham group at the transcriptional level. GO (Gene Ontology) and KEGG (Kyoto Encyclopedia of Genes and Genomes) analysis revealed that stress/stimulus/immune-related biological processes played a crucial role during arterial remodeling. Our data provide a comprehensive understanding of global gene expression changes in the TAC model, which suggests that targeting inflammation and vascular smooth cell transformation are potential therapeutic strategies to interfere with the aortic remodeling at an early stage in the development of hypertension.